2017
DOI: 10.1039/c6ra25901d
|View full text |Cite
|
Sign up to set email alerts
|

Cichoric acid regulates the hepatic glucose homeostasis via AMPK pathway and activates the antioxidant response in high glucose-induced hepatocyte injury

Abstract: CA regulates hepatic glucose homeostasisviathe AMPK pathway and improves hepatocyte injuryviaantioxidant responsein vitroandin vivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
37
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 47 publications
4
37
0
Order By: Relevance
“…The present work has proved that EGCG eliminate the decreased phosphorylation of AMPK, subsequently promoted the membrane translocation of GLUT in glucosamine treated HepG2 cells and primary hepatocytes (Figures E and L). GSK‐3 is implicated with gluconeogenesis, whose inactivation is mediated by both phosphorylation of AKT and AMPK . The results presented in this study clearly showed EGCG markedly elevated the phosphorylated levels of GSK‐3β and decreased CREB phosphorylation, which was enhanced by AICAR and blocked by compound C. These results indicate that the AKT and AMPK signaling pathway are involved in the salutary action of EGCG under insulin resistance conditions (Figures and ).…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…The present work has proved that EGCG eliminate the decreased phosphorylation of AMPK, subsequently promoted the membrane translocation of GLUT in glucosamine treated HepG2 cells and primary hepatocytes (Figures E and L). GSK‐3 is implicated with gluconeogenesis, whose inactivation is mediated by both phosphorylation of AKT and AMPK . The results presented in this study clearly showed EGCG markedly elevated the phosphorylated levels of GSK‐3β and decreased CREB phosphorylation, which was enhanced by AICAR and blocked by compound C. These results indicate that the AKT and AMPK signaling pathway are involved in the salutary action of EGCG under insulin resistance conditions (Figures and ).…”
Section: Discussionsupporting
confidence: 61%
“…Insulin resistance, a complex metabolic disorder and one of the most common chronic diseases, has long been considered to be central to the pathophysiology of metabolic syndrome . Importantly, as the center of peripheral glucose homeostasis and insulin sensitivity, the liver plays an essential role in the systemic insulin resistance and the regulation of blood sugar levels . In the liver, insulin resistance is defined as decreased sensitivity to insulin, which impairs insulin‐dependent inhibition of gluconeogenesis, defective insulin signal transduction and increased expression, and action of proteins involved in lipid synthesis and storage …”
Section: Introductionmentioning
confidence: 99%
“…To evaluate the mechanistic actions behind TQ-induced insulin sensitivity, we used the HepG2 cell line as an in vitro model of insulin resistance to assess whether this action is SIRT-1-dependent. HepG2 cells were made insulin resistant as previously described [ 18 , 19 ], which was confirmed by decreased p-Akt protein after high glucose treatment ( Fig 9A and 9B ). TQ increased p-Akt in high-glucose treated cells, restoring these levels to that of the control cells ( Fig 9A and 9B ).…”
Section: Resultsmentioning
confidence: 55%
“…HepG2 human hepatoma cell line was purchased from American Type Culture Collection (ATCC, Manassas, VA) and cultured in DMEM medium supplemented with 10% FBS, 100 units of penicillin, and 100 μg/mL streptomycin at 37°C in a humified incubator with 5% CO 2 . Cells were made insulin resistant by treatment with 20mM glucose for 18 hours, as previously described [ 18 , 19 ]. Following high glucose treatment, cells were starved for 2 hours in serum-free medium, prior to treatment with the respective compounds for 24 hours.…”
Section: Methodsmentioning
confidence: 99%
“…AMPK and SIRT1 levels in TAA-induced hepatic cirrhosis Di et al (2017). stated that cichoric acid (CA) amplified pAMPK level, activated the nuclear receptor factor-2 (Nrf2), a master regulator of antioxidant enzymes with increasing antioxidant enzymes expression as NQOR1 Eo, Park, Jeon, & Lim, 2017.…”
mentioning
confidence: 99%